P.079 4H leukodystrophy: a case series of siblings with an unusually mild phenotype. (5th June 2019) - DeGasperis, SM; Bernard, G; Pohl, D
Abstract : Background: 4H leukodystrophy is a genetic disorder typically characterized by hypomyelination, hypodontia and hypogonatotropic hypogonadism. Previously reported patients had considerable cognitive and motor deficits. We present a pair of siblings with a less severe phenotype.Methods: Patient data was obtained from medical records from the Children's Hospital of Eastern Ontario.Results: The first patient was diagnosed with 4H leukodystrophy at the age of 21 years after genetic testing revealed a POLR3B mutation with a homozygous V523E variant. She has hypomyelination on MRI and a history of optic neuritis, as well as intermittent sensory and motor symptoms in the context of a diagnosis of multiple sclerosis. She has no clinical manifestations of 4H leukodystrophy. The patient is now 26 years old and has only mild neurological deficits. Her younger brother was diagnosed with 4H leukodystrophy at the age of 18 years and found to have the same genetic mutation as his sister. He has a history of seizures and mild learning disabilities. He is now 23 years old with no typical symptoms of 4H leukodystrophy.Conclusions: 4H leukodystrophy is usually associated with a severe, disabling phenotype and a poor prognosis. Our patients illustrate that a much milder phenotype exists.